Clonorchis sinensis infection modulates key cytokines for essential immune response impacted by sex - Shuo Kan; Qi Li; Hong-Mei Li; Yan-Hua Yao; Xin-Yue Du; Chen-Yun Wu; Guang-Jie Chen; Xiao-Kui Guo; Men-Bao Qian; Zhao-Jun Wang (Public Library of Science (PLoS), 2022)
Infection with helminths can modulate the host immune response, which ultimately shape morbidity and mortality of the associated diseases. We studied key cytokines for essential immune response in sera from 229 southeastern China individuals infected with Clonorchis sinensis and 60 individuals without C. sinensis infection, and measured serum specific IgG and IgE against worms in these people. Individuals infected with C. sinensis had significantly higher antigen-specific IgG and IgE levels, which were positively correlated with egg counts in feces. However, less enhancement of IgE antibody was observed in females when compared to males with similar infection levels. C. sinensis infection caused diminished Th1 cytokines (IL-1β, IL-2, IL-12p70, IFN-γ and TNF-α), Th2 cytokine (IL-4), as well as Th17 cytokine (IL-17A) in sera, which showed decreasing trend by infection intensity. Notably, these phenotypes were more significant in females than those in males. Although C. sinensis infection is associated with the development of hepatobiliary diseases, there was no significant correlation between the dampened cytokine profiles and the hepatobiliary morbidities. Our study indicates C. sinensis infection is strongly related to the immune suppression in human. Sex differences shape the immune milieus of clonorchiasis. This study provides a better understanding of how worms affect immune responses and cause a long-term immune alternation in humans with C. sinensis infection. Author summary Clonorchis sinensis, also known as the liver fluke, lives in human bile duct system and is endemic in East Asia. Chronic C. sinensis infection without treatment can result in serious illness and predispose the human to bile duct cancer. Helminth infection is able to modulate the host immune response and influence the outcome of infection, but the immune characteristics of C. sinensis infection is not yet known. In this study, we analyzed serum samples from individuals living in endemic areas with clonorchiasis in China. We found C. sinensis infection caused increased specific IgG and IgE to adult worm antigens, but diminished levels of key cytokines for essential immune response. Th1 cytokines (IL-1β, IL-2, IL-12p70, IFN-γ and TNF-α), Th2 cytokine (IL-4), as well as Th17 cytokine (IL-17A) showed decreasing trend by infection intensity. Moreover, females exhibited more significant cytokine variation compared to males with similar infection intensity. Our study indicates that C. sinensis infection is related to immune suppression in human, which might contribute to the outcome of clonorchiasis. The sexual dimorphism needs to be considered in the clonorchiasis prophylaxis and immune investigation.